Modelling Water Courses Pollution Near Livestock Farms Using Advanced Hydroinformatic Tools - Erika Beilicci; Camelia Stefanescu; Robert Beilicci (Scientific Papers Animal Science and Biotechnologies, 2023)
Animal husbandry is one of the main causes of water resources pollution: groundwater, water courses and lakes. The achievement of a reliable system of collection, treatment and evacuation/storage of wastewater and animal manure resulting from the process of animal husbandry has a special importance for reducing the impact of livestock farms on environmental factors (water, air, soil). Accidents can occur during operation of these systems and wastewater and animal manure can reach into nearby water courses, determining their pollution. This is a serious problem, especially if the water taken downstream for different use: drinking water or industrial supply, water for irrigation, recreation etc. This paper aims to present a way to model the spread of pollutants in water course in the vicinity of livestock farms, using the PMWIN software, an advanced hydroinformatic tool. On the basis of the results obtained from the modelling, the competent authorities can determine the degree of the pollution and the necessary measures to be taken to reduce the negative effects on water quality.